Statement on imaging and pulmonary hypertension from the Pulmonary Vascular Research Institute (PVRI). (September 2019) - Kiely, David G.; Levin, David L.; Hassoun, Paul M.; Ivy, Dunbar; Jone, Pei-Ni; Bwika, Jumaa; Kawut, Steven M.; Lordan, Jim; Lungu, Angela; Mazurek, Jeremy A.; Moledina, Shahin; Olschewski, Horst; et al.
Pulmonary hypertension (PH) is highly heterogeneous and despite treatment advances it remains a life-shortening condition. There have been significant advances in imaging technologies, but despite evidence of their potential clinical utility, practice remains variable, dependent in part on imaging availability and expertise. This statement summarizes current and emerging imaging modalities and their potential role in the diagnosis and assessment of suspected PH. It also includes a review of commonly encountered clinical and radiological scenarios, and imaging and modeling-based biomarkers. An expert panel was formed including clinicians, radiologists, imaging scientists, and computational modelers. Section editors generated a series of summary statements based on a review of the literature and professional experience and, following consensus review, a diagnostic algorithm and 55 statements were agreed. The diagnostic algorithm and summary statements emphasize the key role and added value of imaging in the diagnosis and assessment of PH and highlight areas requiring further research.